Water sorption and water‐resistance properties of poly(vinyl alcohol)/clay nanocomposite films: Effects of chemical structure and morphology. Issue 4 (19th March 2014) - Lim, Mijin; Kim, Dowan; Han, Haksoo; Khan, Sher Bahadar; Seo, Jongchul
Abstract : A series of poly(vinyl alcohol)/sodium montmorillonite (PVA/NaMMT) nanocomposite films were prepared via a solution method, and their water sorption and water‐resistant properties were investigated as a function of clay content. The water sorption and water resistance properties were strongly dependent on the chemical structure and film morphology originating from the NaMMT content. The water diffusion coefficient and water uptake of the PVA/NaMMT nanocomposite films were obtained by best fits to a Fickian diffusion model. The diffusion coefficient and water uptake in the PVA/NaMMT nanocomposite films varied between 8.16 × 10 −10 and 3.60 × 10 −10 cm 2 s −1 and 35.6 and 29.9 wt%, respectively. Both the diffusion coefficient and water uptake decreased as the content of NaMMT in pure PVA was increased. Additionally, the water resistance pressure (mm) of the PVA/NaMMT nanocomposite films increased with increasing NaMMT content. Contact angle analyses showed that the chemical affinity to water and the surface energy of the nanocomposite films decreased with increasing NaMMT content. Furthermore, the well‐dispersed and exfoliated structure in the nanocomposite films not only induced an increased tortuous path for water molecules to pass through, but also increased the molecular order. However, to enhance the water sorption properties and water resistance of hydrophilic PVA, further studies to increase the dispersion of clay particles and ensure desired morphological qualities such as crystallinity and molecular packing order in the PVA/clay nanocomposite films are required. POLYM. COMPOS., 36:660–667, 2015. © 2014 Society of Plastics Engineers